EDUCATIONAL SERVICES AS A FACTOR OF SOCIO-ECONOMIC DEVELOPMENT OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article examines the socio-economic significance of educational services in the development of Uzbekistan’s economy. Special attention is paid to the role of education in the formation of human capital, the training of a qualified workforce, the improvement of national competitiveness and the enhancement of living standards. The paper also considers strategic initiatives of the Republic of Uzbekistan aimed at reforming the education system, developing the private sector of educational services and introducing information and communication technologies into the educational process.
Keywords: education, educational services, human capital, investment in human capital, investment in the future, qualified workforce, labor market, subjects of educational services, objects of educational services, personal development, public educational institutions, paid educational services.